Research on gasification of low-grade fuels in a continuous layer - Mysak, Joseph; Lys, Stepan; Martynyak-Andrushko, Marta (Eastern-European Journal of Enterprise Technologies, 2017)
The technology of thermal processing of low-grade fuel into gaseous fuel is an essential problem whose solution will create clean energy as an alternative to natural gas and coal gasification. It also can solve the problems of the ecological utilization of industrial and household waste as well as of obtaining cheap energy and improving industrial effects for the environment. The analysis of the theoretical provisions and experimental tests has proved the possibility of processing wood during its gasification in a gas generator with a continuous layer; it is processed into gaseous fuel with the lower calorific value being 1.5 times higher in comparison with the calorific value of the gaseous fuel that is produced by other known gas generators of this type. The experimental results have specified the regression dependence of heat that is produced by burning the synthesis gas during the gasification of low-grade fuel on the fractional composition of the fuel, the amount of air, and the fuel layer height. The resulting regression equations can be the basis for implementing the studied process and its rational management. The equations of the input factors’ dependence on the original setting make it possible to determine every possible parameter of assessing the process under study at any value of the factors between the upper and lower levels. The tests have revealed the rational values of the input parameters for operating a gas generator with a continuous layer at which the lower heating value of burning the syngas reaches its maximum.